sort by best latest
The nth term of the sequence 1, 12, 23, 34
Tn = a + (n - 1) d
a = 1
d = 12 - 1 = 11
Tn = 1 + (n - 1) x 11
Tn = 1 + 11n - 11
Tn = 11n - 10 ( This is the Answer)
It can also be written as Un = 11n - 10
You can help the HubPages community highlight top quality content by ranking this answer up or down.
Copyright © 2017 HubPages Inc. and respective owners. Other product and company names shown may be trademarks of their respective owners. HubPages® is a registered Service Mark of HubPages, Inc. HubPages and Hubbers (authors) may earn revenue on this page based on affiliate relationships and advertisements with partners including Amazon, Google, and others.
Copyright © 2017 HubPages Inc. and respective owners.